Analisis Tindak Tutur Ekspresif Pembelajaran Daring Bahasa Indonesia dalam Kanal YouTube SMKN 1 Sindang - Uswatun, Fika; Lythia, Syahulla Barta; Hasanatika, Ikvina; Octavianti, Aisyiah Syiam; Utomo, Asep Purwo Yudi (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The video review of the online learning process of subjects Indonesian class X to XII SMK N 1 Sindang uploaded on social media Youtube was carried out to analyze the diversity of expressive speech acts used when the learning process was taking place. The assessment technique carried out is listening, namely the researcher listens to the conversation between speakers and speech partners in the learning process. The online learning video assessment method is descriptive qualitative which is chosen to present the results of the analysis without a measurement process and then described in detail according to the pragmatic review. The results obtained from the analysis of expressive speech acts carried out on the video are speech acts of greeting and asking for news, speech acts of telling and commanding, speech acts of praise, speech acts of asking, acts of thanking speech, acts of mocking speech, acts of wishing and reminding, acts of calling speech, acts of convincing speech, acts of motivating speech, acts of insinuating speech, acts of apologizing speech, acts of wishing, acts of respectful speech, as well as acts of speech of refusing and complaining.